2009
DOI: 10.1177/1076029609334627
|View full text |Cite
|
Sign up to set email alerts
|

Increased Thrombophilic Tendency in Pediatric Cystic Fibrosis Patients

Abstract: Thrombophilia has recently been reported to be increased in patients with cystic fibrosis (CF). We wanted to determine whether this was applicable to our population with CF and how our patients compared to the previously reported groups. Seventy one pediatric CF patients were assessed for a thrombophilic tendency, using a lupus anticoagulant screen, protein C, protein S, antithrombin assay, and activated protein C resistance (APCR) screen. The incidence of activate protein C resistance (4.2%) was within expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Balfour-Lynn et al also reported greater than expected rates of protein C deficiency (4 vs. 0.2–0.4%) and protein S deficiency (5 vs. 0.3%) in addition to anti-thrombin deficiency (1 vs. 0.2%) and lupus anticoagulant deficiency (9 vs. 1–5%) in CF patients compared to the general population ( 13 ). This study of 204 CF patients was conducted in asymptomatic patients in an out-patient setting, and thus, did not investigate levels in patients with confirmed VT. Another study of 71 patients concurred with Balfour-Lynn et al reporting elevated rates of lupus anti-coagulants (18%), protein C deficiency (14%), and protein S deficiency (19.7%) ( 14 ). Anti-phospholipid antibody levels have also been noted to be raised in children with CF (4–9.5 vs. 1–3%) ( 15 , 16 ).…”
Section: Discussionsupporting
confidence: 53%
“…Balfour-Lynn et al also reported greater than expected rates of protein C deficiency (4 vs. 0.2–0.4%) and protein S deficiency (5 vs. 0.3%) in addition to anti-thrombin deficiency (1 vs. 0.2%) and lupus anticoagulant deficiency (9 vs. 1–5%) in CF patients compared to the general population ( 13 ). This study of 204 CF patients was conducted in asymptomatic patients in an out-patient setting, and thus, did not investigate levels in patients with confirmed VT. Another study of 71 patients concurred with Balfour-Lynn et al reporting elevated rates of lupus anti-coagulants (18%), protein C deficiency (14%), and protein S deficiency (19.7%) ( 14 ). Anti-phospholipid antibody levels have also been noted to be raised in children with CF (4–9.5 vs. 1–3%) ( 15 , 16 ).…”
Section: Discussionsupporting
confidence: 53%
“…Thrombophilia is reported in diabetic patients in the general population [21][22][23], presumably on the basis of a proinflammatory state. A thrombophilic state may also pertain in CF, in part due to vitamin K deficiency, which can associate with protein C or S deficiency [24][25][26][27]. Increased frequency of venous thrombosis has been reported in children [28] and adults [29] with B. cepacia spp.…”
Section: Risk Factors For Picc Complicationsmentioning
confidence: 99%
“…The incidental discovery of a non-occlusive aortic thrombus in the aortic segment of the liver-pancreas graft highlights a potential drawback of this technique. Although some reports link CF with hypercoagulability [19,20], we believe that stasis, particularly at the blind-stapled end of the supra-celiac aorta, was the main contributing factor. Reconstruction of the celiac and superior mesenteric arteries with a donor iliac artery Y-graft, as described by Young et al [12], might reduce this risk.…”
Section: Discussionmentioning
confidence: 73%